Comparison of pain and proper sample status according to usage of tenaculum and analgesia: a randomized clinical trial - Cihan Comba; Gökhan Demirayak; Sakir Volkan Erdogan; Ibrahim Karaca; Omer Demir; Oguz Guler; Isa Aykut Ozdemir (Korean Society of Obstetrics and Gynecology, 2020)
Objective Colposcopic biopsy is a discomfortable procedure. Additionally, it creates negative influence on sexuality. This study aimed to investigate the relationships among tenaculum, pain perception, and biopsy size during colposcopy. Methods In total, 228 patients who underwent colposcopy-directed biopsy were included, and randomized into 4 groups based on whether analgesic and tenaculum were used and replaced (tenaculum with n=58/without analgesic n=56, no tenaculum replacement with n=57/without analgesic n=57). Lidocaine hydrochloride (40 mg) plus adrenaline (0.025 mg) was administered in the analgesic groups. The pain was assessed using a linear visual analog scale. The biopsy specimen size was measured in millimeters. Results The mean age of the patients was 42.85±8.88 years. The most frequent colposcopy indications were atypical squamous cells of undetermined significance and human papilloma virus-positive results on cervical cytology (30.2%; n=69). Low- and high-grade intraepithelial lesions were noted in 14.91% (n=34) and 10.96% (n=25) women through colposcopy-directed biopsy results, respectively. Tenaculum replacement increased pain perception in the without analgesic group; however, no statistically significant differences were noted between of the groups with and without tenaculum replacement with analgesic. The size and number of biopsy specimens were not associated with tenaculum replacement and analgesic use. Conclusion Administration of analgesics decreased discomfort and pain in patients. Tenaculum replacement aided colposcopists in manipulating the cervix. Additionally, administration of analgesics relieved pain in the tenaculum replacement group. Trial Registration ClinicalTrials.gov Identifier: NCT03279666